Laser weldable polyester compositions, their preparation and process and their use

The balance between laser light transparency and mechanical properties is solved by using polybutylene terephthalate resin (PBT), glass fibers and alkali metal salts of fatty acids with 24-40 carbon atoms in the fiber-reinforced polyester composition, and a composition with high transparency and good mechanical properties is achieved.

CN119677631APending Publication Date: 2025-03-21恩骅力有限公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380057800.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-12
Filing Date
2023-08-01
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a good balance between laser light transparency and mechanical properties, especially in the application of polyester compositions, and methods of increasing laser light transparency generally reduce mechanical properties.

Method used

A fiber-reinforced polyester composition is employed which comprises a polybutylene terephthalate resin (PBT), glass fibers and alkali metal salts of fatty acids with 24-40 carbon atoms. The composition is prepared by melt mixing, and the addition of component (C) significantly improves laser light transparency while maintaining a high level of mechanical properties.

Benefits of technology

An improved balance between laser light transparency and mechanical properties is achieved, significantly increasing laser light transparency and shortening laser welding cycle time while maintaining good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005261255410000181
    Figure BDA0005261255410000181
  • Figure BDA0005261255410000191
    Figure BDA0005261255410000191
  • Figure BDA0005261255410000192
    Figure BDA0005261255410000192
Patent Text Reader

Abstract

The present invention relates to a laser weldable polyester composition, and more particularly, to a laser weldable fiber-reinforced polybutylene terephthalate composition, the composition comprising: (A) a polybutylene terephthalate resin (PBT); (B) glass fibers; and (C) an alkali metal salt of a fatty acid having 24 to 40 carbon atoms; wherein the component (B) is present in an amount in the range of 15-100 parts by weight with respect to 100 parts by weight of the component (A), and the component (C) is present in an amount in the range of 1.75-4.5 parts by weight with respect to 100 parts by weight of the component (A). The invention also relates to a method for producing a laser weldable fiber-reinforced polyester composition, to a method for producing a molded part from a laser weldable fiber-reinforced polyester composition, to a laser transparent molded part made of a laser weldable fiber-reinforced polyester composition, and to a method for producing a laser transparent molded part made of a laser weldable fiber-reinforced polyester composition. A method of laser welding a laser transparent molded part made of a laser weldable fiber-reinforced polyester composition onto a laser light-absorbing polymer substrate, and a composite article, a molded article comprising a laser weldable fiber reinforced polyester composition bonded by laser welding on a laser ray absorbing polymer substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laser-weldable polyester composition, and more particularly to a laser-weldable fiber-reinforced polyester composition comprising a polybutylene terephthalate resin and glass fibers.

[0002] - A method for preparing a laser-weldable fiber-reinforced polyester composition;

[0003] - A method for producing a moulded part from a laser-weldable fibre-reinforced polyester composition;

[0004] - a laser-transparent moulding made of a laser-weldable fibre-reinforced polyester composition;

[0005] - a method for laser welding a laser-transparent molding made of a laser-weldable fiber-reinforced polyester composition to a laser-light-absorbing polymer substrate; and

[0006] - A composite article comprising a molded article made of a laser-weldable fiber-reinforced polyester composition, the molded article being bonded to a laser-light-absorbing polymer substrate by laser welding. Background Art

[0007] There are various methods for welding plastic molds, such as heat tool welding, vibration welding and laser welding. Laser transmission welding is an alternative to vibration welding and heat tool welding, and its use has been increasing in recent years, especially the use of diode lasers. Laser weldable polyester compositions are known in the prior art and are described in various patents or patent applications.

[0008] US2008153957 describes a laser weldable polyester composition. The composition of US2008153957 comprises (A) polybutylene terephthalate (PBT) resin and (B) fatty acid compound, and the amount of (B) fatty acid compound is in the range of 0.01 to 1.0 parts by weight (pbw) relative to 100 pbw of PBT resin, preferably about 0.03 to 0.5 pbw. The fatty acid compound is suitably a metal salt of a fatty acid ester, a fatty acid amide or a C12-36 fatty acid. The metal salt of C12-36 fatty acid can include, for example, alkali metal salts (such as sodium salts and potassium salts), alkaline earth metal salts (such as magnesium salts and calcium salts), salts of metals of Group 2B of the Periodic Table (such as zinc salts), and salts of metals of Group 3B of the Periodic Table (such as aluminum salts), alone or in combination. According to US2008153957, adding fatty acid series compounds to resin combination in a specific low ratio as described above effectively ensures the improvement of laser transmittance, while with a lower ratio of fatty acid series compounds, the improvement of laser transmittance is not enough, and on the other hand, with a higher ratio of fatty acid series compounds, the laser transmittance is likely to be deteriorated (dereriorated, deteriorated). The composition of US2008153957 may include further components, such as fibers and fillers and other auxiliary additives for PBT-based polyester compositions. The further component mentioned as optional component (C) in the composition of US2008153957 is a cyclic polyester oligomer. However, in the example of US2008153957, component (B) shows a moderate impact on transparency and welding strength, while component (C) shows a smaller additional impact on transparency, but the impact on welding strength is more obvious.

[0009] US2011288220 describes a composition for a laser transparent mold, the composition comprising (A) polyester and (B) sodium carbonate or potassium carbonate or sodium bicarbonate or potassium bicarbonate. The composition may comprise (C) further additives. Component (B) is present in an amount in the range of 0.05 to 2.0wt.% relative to the total weight of the composition, and component (B) is added to enhance the transparency of the laser light. Further additives include reinforcing fibers, lubricants and release agents. As possible lubricants and release agents, long-chain fatty acids and their salts are mentioned. As mentioned in US2011288220, these are used in amounts up to 1wt.%. In US2011288220, a series of composition examples comprising PBT and variable amounts of component (B) additives but without glass fibers, and a series of composition examples comprising PBT, variable amounts of component (B) additives and 30wt.% glass fibers are given. In terms of the amount of component (B), both series show the best laser light transmittance. The first series exhibited the highest laser light transmittance when the amount of component (B) was in the range of 0.4-0.5 wt.%, and the second series exhibited the highest laser light transmittance when the amount of component (B) was in the range of 0.3-0.4 wt.%. These weight percentages corresponded to 0.40-0.50 pbw of component (B) for the first series relative to 100 pbw of PBT resin; and these weight percentages corresponded to 0.42-0.57 pbw of component (B) for the second series relative to 100 pbw of PBT resin. In addition, for all corresponding compositions having the same amount of component (B), the laser light transmittance of the glass fiber reinforced composition was lower than that of the non-reinforced composition.

[0010] Patent application US2012231285 describes the use of thermoplastic molding compositions to produce laser transparent molds, the composition comprising (A) polyester, (B) alkali metal salts of aliphatic carboxylic acids, and optionally (C) further additives. Based on 100% by weight of (A) and (B), the amount of the alkali metal salt (B) is 0.2 to 2% by weight. The composition may include further additives, up to 70wt.% of the composition. The preferred alkali metal in the alkali metal salt of component (B) is potassium and / or sodium. In addition, it is preferably a saturated or unsaturated carboxylic acid having 1 to 40, more preferably 1 to 22 carbon atoms. Multiple examples of compositions based on PBT as component (A) and variable amounts of sodium acetate or sodium stearate as component (B) are given. For sodium acetate or sodium stearate, as the amount of the alkali metal salt of aliphatic carboxylic acid (B) increases up to a level of about 0.8-1.0 wt.%, the laser light transparency increases significantly, while above this amount, the laser light transparency level increases or the laser light transparency even decreases. At the same time, up to a level of about 0.8-1.0 wt.%, the tensile strength remains approximately constant, but above this amount, the tensile strength decreases. Moreover, already with the addition of a small amount of sodium acetate or sodium stearate, the tensile strain at break decreases sharply, and with increasing amounts of sodium acetate and sodium stearate, the tensile strain at break further decreases systematically.

[0011] In general, there is a need for a laser weldable composition, in particular a laser weldable polyester composition, which has high laser light transparency and good weldability as well as good mechanical properties, in particular tensile strength, elongation at break and impact strength. Although mechanical properties can be enhanced by adding reinforcing agents, such components reduce laser light transparency. On the other hand, the addition of laser light transparency enhancing additives not only has its own limitations in terms of the effect on laser light transparency, but also, as indicated above, has an undesirable negative impact on the mechanical properties of PBT-based polyester compositions. Summary of the invention

[0012] Therefore, the object of the present invention is to provide a laser-weldable polyester composition, more particularly a laser-weldable fiber-reinforced polyester composition, which has an improved balance between laser light transparency and mechanical properties, and preferably has both good laser light transparency and good mechanical properties.

[0013] This object is achieved using a fiber-reinforced polyester composition according to the present invention, which comprises: (A) a polybutylene terephthalate resin (PBT); (B) glass fibers; and (C) an alkali metal salt of a fatty acid having 24 to 40 carbon atoms. The glass fibers (component (B)) are present herein in an amount ranging from 15 to 100 parts by weight relative to 100 parts by weight of PBT (component (A)). The alkali metal salt of a fatty acid having 24 to 40 carbon atoms (component (C)) is present herein in an amount ranging from 1.75 to 4.50 parts by weight relative to 100 parts by weight of component (A). DETAILED DESCRIPTION

[0014] The composition according to the invention, comprising component (C) in the amount described, has the effect of significantly increasing the laser light transparency, allowing a significant reduction in the laser welding cycle time, while the mechanical properties remain at an outstanding level. More particularly, the increase in laser light transparency exceeds the increase expected on the basis of an increase of 1 pbw of component (C), while with regard to mechanical properties, more particularly tensile strength, elongation at break and / or unnotched impact properties, although lower than the mechanical properties of the corresponding composition without component (C), the reduction is much smaller than that of the corresponding composition comprising, for example, the same amount of sodium stearate or sodium myristate instead of component (C). In addition, the laser light transparency is increased more than the corresponding metal salts of C24-C40 fatty acids based on other metals, such as magnesium (a metal in the alkaline earth metal group) and aluminum (a metal in group 3B of the periodic table).

[0015] It should be noted that, in the statement of referring to a range with an upper limit and / or a lower limit, the range explicitly includes any value within the range as well as the upper limit and the lower limit mentioned. For example, "an amount in the range of 1.75-4.50 parts by weight", the range explicitly includes 1.75 and 4.50 and any value between 1.75 and 4.50.

[0016] It should be noted that during the preparation of the composition of the present invention, wherein components (A), (B) and (C) are mixed, for example by melt mixing, some reaction may occur between the polybutylene terephthalate resin (PBT; component (A)) and the alkali metal salt of a fatty acid (component (C)). Therefore, in the composition according to the present invention, component (A) and component (C) may be present as a reaction product resulting from a reaction between component (A) and component (C). For example, reactions that may occur are transesterification and salt exchange, etc.

[0017] In the transesterification reaction, the terephthalic acid carboxyl groups and the fatty acid carboxyl groups may be exchanged, resulting in the fatty acid carboxyl groups being incorporated into the polyester chain as terminal groups, and the polyester chain having an alkali metal salt of a carboxylic acid terminal group, as shown in reaction (I):

[0018] R PBT-1 -O-(O)C-C6H4-C(O)-OR PBT-2 +MO-(CO)-R FA →

[0019] R PBT-1 -O-(O)CR FA +MO-(CO)-C6H4-C(O)-OR PBT-2 (I)

[0020] In a salt exchange reaction (also called an ion exchange reaction), the protonated carboxylic acid end groups (including protons (H) and carboxylic acid groups (R PBT -C(O)-O)) with an alkali metal salt of a fatty acid (comprising an alkali metal ion (M) and a carboxyl group (OC(O)-R FA )) may react with each other, in which protons and alkali metal ions are exchanged to produce protonated fatty acids HO-(CO)-R FA and a polyester chain with an alkali metal salt of a carboxylic acid end group, as shown in reaction (II):

[0021] R PBT-3 -O-(O)C-C6H4-C(O)-OH+MO-C(O)-R FA →

[0022] R PBT-3 -O-(O)C-C6H4-C(O)-OM+HO-C(O)-R FA (II)

[0023] In this paper, R PBT-1 , R PBT-2 and R PBT-3 R represents a polyester chain whose repeating units are derived or mainly derived from a diacid and a diol, more particularly mainly from terephthalic acid and butanediol. FA Represents the fatty acid chain. FA Contains 23-39 carbon atoms, and the corresponding carboxyl functional fatty acid group O-(CO)-R FA Contains 24-40 carbon atoms. MO-(CO)- represents an alkali metal salt of a carboxylic acid group. -C(O)-OH represents a protonated carboxylic acid group. -C6H4- represents an aromatic ring of a terephthalic acid group.

[0024] Therefore, in the composition according to the present invention, component (A) and component (C) may be present in the form of themselves, or in the form of their reaction products, or in the form of a combination thereof (i.e., partly in the form of themselves and partly in the form of their reaction products). In the present invention described herein, the amounts of component (A) and component (C) are expressed in wt.% or parts by weight, and the amount of component (C) refers to the alkali metal ion (M; by adding the component MO-(CO)-R FA and C24-C40 carboxyl functional fatty acid groups O-(CO)-R FA The total weight of component (A) is excluding any protonated and / or esterified groups attached thereto; and the amount of component (A) refers to the total weight of the components in the polyester chain, excluding any alkali metal ions or carboxyl functional C24-C40 fatty acid groups therein. In other words, for the sake of clarity: the bold parts in the following structures are included in the amount of component (A), while the underlined parts are included in the amount of component (C):

[0025] (Polyester chain),

[0026] (polyester chains with protonated carboxylic acid groups),

[0027] M (polyester chains with pendant alkali metal ions),

[0028] R FA -C(O)-O - , (polyester chain with pendant carboxyl functional C24-C40 fatty acid groups),

[0029] R FA -C(O)-O-M (alkali metal salts of C24-C40 fatty acids); and

[0030] R FA -C(O)-O - (Protonated C24-C40 carboxyl functional fatty acid groups).

[0031] This amount is determined by the amounts of the components used in the preparation of the composition and can be prepared by techniques known to those skilled in the art using hydrolysis, acidification, 1 H-NMR solution spectroscopy and HPLC or GC quantification in compositions or injection molded parts.

[0032] An example of an alkali metal salt of a fatty acid having 24-40 carbon atoms is sodium montanate: MO-(CO)-C27H55, wherein M is sodium (Na; molar mass = 22.99) and the carboxylic acid function is C28H25O2 (molar mass = 423.75 g / mol).

[0033] For example, polymer compositions comprising PBT and sodium montanate are known from US2010 / 0227182. The patent application describes a polyester composition comprising PBT or other thermoplastic polyesters and sodium montanate, and is generally non-reinforced. The polyester composition can be used for sunshade (bezel, bezel, frame) applications. The sodium montanate used herein is used as a lubricant, and its amount is 0.01 to 0.5wt.% based on the total weight of the composition. US2010 / 0227182 focuses on the low outgassing of sunshades, and does not mention any polymer welding behavior, laser light transparency or the influence of sodium montanate on the mechanical properties of molded parts made of fiber-reinforced compositions.

[0034] Component (A) in the composition according to the present invention is a polybutylene terephthalate (PBT) resin. The PBT resin may be any thermoplastic polybutylene terephthalate resin suitable for use in a fiber-reinforced polymer composition and is known in the art, and the fiber-reinforced polymer composition is suitable for making fiber-reinforced molded parts in a molding process.

[0035] The polybutylene terephthalate resin is suitably a PBT homopolymer or a PBT copolymer. The PBT homopolymer is mainly composed of copolymerized units of butene and terephthalate. Such homopolymers can be suitably prepared by copolymerization of butanediol and terephthalic acid, wherein these monomers are used as the sole monomers. The PBT homopolymer may contain other copolymerized units produced in trace amounts by other components; for example, trace impurities in butanediol and / or terephthalic acid, or trace impurities formed during the polycondensation of butanediol and terephthalic acid. Suitably, the PBT homopolymer is composed of at least 99 mol % of butene units and terephthalate units and at most 1 mol % of other copolymerized units relative to the total molar amount of butene units, terephthalate units and other copolymerized units.

[0036] The PBT copolymer can include other comonomers and such comonomers can be copolymerized in copolymer chains with less amount. The example of such other comonomers includes difunctional monomers (i.e. monomers with two reaction sites), such as other diacids (such as isophthalic acid), other glycols (such as ethylene glycol) and functional comonomers (such as sodium 5-sulfoisophthalic acid). If any, the amount of difunctional comonomers is suitably up to about 10mol%, or up to about 5mol% amount exists. Comonomers with more than two reaction sites, such as trimellitic anhydride, trimellitic acid, pyromellitic acid dianhydride (pmda) and pentaerythritol, can be suitably added as branching agent, to increase melt viscosity. If any, such comonomers with more than two reaction sites are suitably up to about 5mol%, or even better up to about 2.0mol% amount exists. Suitably, the PBT copolymer contains at least about 85 mol% of butene copolymerized units (butene units) and terephthalate copolymerized units (terephthalate units) and up to about 15 mol% of copolymerized units of further comonomers (comonomer units). Examples of further comonomers that can be copolymerized into the PBT copolymer are, for example, isophthalic acid, propylene glycol, and butanediol. Preferably, the PBT copolymer contains at least about 90 mol%, more preferably at least about 95 mol%, or even more preferably at least about 98 mol% of butene units and terephthalate units; and correspondingly preferably up to about 10 mol%, more preferably up to about 5 mol%, or even more preferably up to about 2.0 mol% of comonomer units. Herein, the molar percentages (mol%) of butene units, terephthalate units, and comonomer units are all relative to the total molar amount of the moles of butene units, the moles of terephthalate units, and the moles of comonomer units in the copolymer.

[0037] In a preferred embodiment of the composition of the present invention, the PBT resin is a PBT homopolymer, or a PBT copolymer containing at least 98 mol% of copolymerized units of butene and terephthalate and up to about 2.0 mol% of copolymerized units of a comonomer, the amounts being the total molar amount relative to the molar number of butene units, the molar number of terephthalate units and the molar number of comonomer units in the copolymer.

[0038] The polybutylene terephthalate resin (A) used to prepare the composition according to the present invention can be any polybutylene terephthalate resin commonly used for preparing thermoplastic polyester molding compositions. The resin may have correspondingly varying properties, such as viscosity and melt flow ratio. Suitably, the polybutylene terephthalate resin has a relative solution viscosity as high as about 2.8, or even higher than 2.8, or as low as about 1.5, or even lower than 1.5. Preferably, the PBT resin has a RSV in the range of 1.8-2.6, more preferably in the range of 2.0-2.5. In this article, relative solution viscosity (RSV) is measured in meta-cresol at a temperature of 25°C, with a concentration of 1g in 100g of meta-cresol, according to the method of ISO 307.

[0039] The advantage of a PBT resin with a lower viscosity is that the laser-weldable fiber-reinforced polyester composition has an improved processing behavior, while the advantage of a PBT resin with a higher viscosity is that a molded part made from the composition has better mechanical properties. The advantage of a PBT resin with a viscosity in the preferred range is that the composition combines good processing behavior with good mechanical properties. The advantage of a PBT resin with a viscosity in the more preferred range is that the composition has an even better balance between processing behavior and mechanical properties.

[0040] In a preferred embodiment, the PBT resin in the laser weldable fiber reinforced polyester composition has a relative solution viscosity (RSV) of 2.4 or less. Based on experimental values, the advantage is an improved welding process, i.e., a shorter cycle time is required to achieve a certain bond strength, or a higher bond strength is obtained in the same cycle time compared to a composition containing a corresponding PBT resin with a higher viscosity.

[0041] Suitably, the laser weldable fiber reinforced polyester composition comprises component (A) in an amount ranging from 40 to 85 wt.%, relative to the total weight of the composition. The amount may be, for example, as low as or about 45 wt.%, 50 wt.%, 55 wt.% or 58 wt.%, or as high as or about 80 wt.%, 75 wt.% or 70 wt.%, relative to the total weight of the composition.

[0042] For the glass fiber of component (B), any glass fiber suitable for use in a fiber-reinforced polyester composition and suitable for use in a molding process for manufacturing a fiber-reinforced molded part from such a composition can be used. Suitable glass fibers are known in the art. The glass fibers used to manufacture the laser-weldable fiber-reinforced polyester composition according to the present invention can have a length that varies over a wide range. These can be used in the form of commercially available rovings or chopped glass. The glass fibers can be added as continuous fibers or cut or milled glass fibers, and the fibers can be provided with a suitable sizing system and a bonding promoter or bonding promoter system, for example based on silane. Glass fibers in the form of E-glass (aluminoborosilicate glass containing less than 1 wt.% of alkali oxides, mainly used for glass reinforced plastics) are particularly preferred, but other types of glass fibers can also be used, such as A-glass (soda-lime glass containing little or no boron oxide), E-CR-glass (alumino-lime silicate containing less than 1 wt.% of alkali oxides, with high acid resistance), C-glass (soda-lime glass with a high boron oxide content, for example for glass short fibers), D-glass (borosilicate glass with a high dielectric constant), R-glass (aluminoborosilicate glass without MgO and CaO, with high mechanical requirements) and S-glass (aluminoborosilicate glass without CaO but with a high MgO content and with high tensile strength). The glass fibers appropriately have a fiber diameter of between 3 and 20 μm (micrometers). The glass fibers can have cross sections of different shapes. The glass fibers appropriately have a circular cross section. These glass fibers can have, for example, a number average diameter of about 7 μm, about 8 μm, or about 9 μm, or about 10 μm, or about 12 μm, or about 15 μm. Preferably, the number average diameter is in the range of 8-15 μm, more preferably in the range of 9-12 μm. Glass fibers can also have a non-circular cross section, such as a rectangular cross section or an elliptical rectangular cross section. The non-circular cross section is characterized in that the cross section has different diameters in different directions in this article. Suitably, the glass fiber with a non-circular cross section has a maximum diameter of, for example, about 5 μm, or about 8 μm, or about 9 μm, or about 10 μm, or about 12 μm, or about 15 μm, or about 18 μm. Preferably, the number average of the maximum diameter is in the range of 9-18 μm, more preferably in the range of 10-15 μm.

[0043] Component (B) (i.e. glass fibers) is present in an amount in the range of 15-100 pbw relative to 100 pbw of component (A). Preferably, the amount of component (B) is in the range of 25-80 pbw, more preferably 30-70 pbw, even more preferably 35-60 pbw relative to 100 pbw of component (A). The advantage of a higher minimum amount of component (B) is that the mechanical properties of the composition are better, more particularly the tensile strength is higher. The advantage of a lower maximum amount of component (B) is that the laser light transparency of the composition is better.

[0044] An example of a composition according to the present invention is a composition consisting of 100 pbw of component (A), 100 pbw of component (B) and 2.0 pbw of component (C). Herein, relative to the total weight of the composition, component (B) is present in an amount of 49.5 wt.%. Another example of a composition according to the present invention is a composition consisting of 100 pbw of component (A), 15 pbw of component (B) and 4 pbw of component (C). Herein, relative to the total weight of the composition, component (B) is present in an amount of 12.6 wt.%. If the composition comprises one or more further components in addition to 100 pbw of component (A), 15 pbw of component (B) and 4 pbw of component (C), the weight percentage of component (B) relative to the total weight of the composition may be lower than 12.6 wt.%, such as 10 wt.%. Suitably, relative to the total weight of the composition, the composition according to the present invention comprises component (B) in an amount within the range of 15-49.5 wt.%. The amount may be, for example, as low as or about 15, 20 or 25 wt.%, or as high as or about 48, 44 or 40 wt.%, relative to the total weight of the composition.

[0045] The metal in the metal salt of component (C) is an alkali metal. The alkali metal is suitably lithium, sodium or potassium, or a combination thereof. Preferably, the alkali metal is sodium or potassium, or a combination thereof, and more preferably consists of sodium.

[0046] The fatty acid in the fatty acid salt of component (C) is suitably a saturated fatty acid or an unsaturated fatty acid, or a combination thereof. The fatty acid may be a straight chain fatty acid or a branched chain fatty acid, or a combination thereof. The fatty acid may contain heteroatoms, such as nitrogen atoms, or may not contain heteroatoms.

[0047] Saturated fatty acids falling within the scope of the present invention and containing no heteroatoms can be represented by the formula C x H 2x O2 represents, where x is an integer in the range of 24-40.

[0048] Preferably, the fatty acid is a straight chain saturated fatty acid containing no heteroatoms. Such preferred straight chain saturated fatty acids containing no heteroatoms can be represented by the formula H3C(CH2): y CO2H, wherein y is an integer in the range of 22-38.

[0049] Examples of suitable linear saturated fatty acids are

[0050] -lignocerinnic acid (lignocerinnic acid) (from C 24 H 48 O2 or H3C(CH2) 22 CO2H represents);

[0051] -pentaconic acid, also known as pentacosanoic acid (formula C 25 H 50 O2 or H3C(CH2) 23 CO2H represents);

[0052] - Ceranoic acid, also known as hexacosanoic acid (formula C 26 H 52 O2 or H3C(CH2) y24 CO2H represents);

[0053] -Montanic acid, also known as n-octacosanoic acid (formula C 28 H 56 O2 or H3C(CH2) 26 CO2H represents);

[0054] - Melissa acid, also known as triacontanic acid (formula C 30 H 60 O2 or H3C(CH2) 28 CO2H represents);

[0055] -Lacceric acid, also known as triacontanic acid (formula C 32 H 64 O2 or H3C(CH2) 30 CO2H represents);

[0056] -Tetratriacontanoic acid (formula C 34 H 68 O2 or H3C(CH2) 32 CO2H represents);

[0057] -Hexatriacontanoic acid (formula C 36 H 72 O2 or H3C(CH2) 34 CO2H); and

[0058] -Tetradecanoic acid (formula C40 H 80 O2 or H3C(CH2) 38 CO2H).

[0059] In a preferred embodiment of the present invention, component (C) is a salt of a fatty acid having 26-36 carbon atoms (also known as C26-C36 fatty acid), more preferably a salt of a fatty acid having 28-32 carbon atoms (also known as C28-C32 fatty acid).

[0060] In a further preferred embodiment of the present invention, component (C) is a sodium salt or potassium salt of a C26-C36 fatty acid, or a combination thereof. More preferably, component (C) is a sodium salt or potassium salt of a C28-C32 fatty acid, or a combination thereof.

[0061] In a more preferred embodiment of the present invention, component (C) is a sodium or potassium salt of a linear saturated C26-C36 fatty acid. Examples thereof are sodium montanate, potassium montanate, sodium triacontanate, potassium triacontanate, sodium docosanoate, potassium docosanoate, sodium hexaconate and potassium hexaconate, and any mixture thereof.

[0062] Component (C) is present in an amount in the range of 1.75-4.50 parts by weight (pbw) relative to 100 pbw of component (A). Suitably, the amount of component (C) is in the range of 1.9-4.0 pbw relative to 100 pbw of component (A). Preferably, component (C) is present in an amount in the range of 2.0-3.75 pbw, more preferably 2.1-3.5 pbw, even more preferably 2.2-3.2 pbw, and most preferably 2.3-3.0 pbw relative to 100 pbw of component (A). The effect of limiting or further limiting the amount of component (C) within the said range is that the laser light transparency at a thickness of 2.0 mm is further increased, while the reduction in mechanical properties is further limited.

[0063] Suitably, the laser-weldable fiber-reinforced polyester composition according to the present invention comprises component (C) in an amount in the range of 1-3.3 wt.%, relative to the total weight of the composition. This is subject to the requirement for the amount of component (C) being also met, in parts by weight, relative to 100 pbw of component (A), the amount of component (C) being 1.75-4.50 parts pbw, or a narrower range where applicable. The amount of component (C) may be, for example, as low as or about 1.1 wt.%, 1.2 wt.%, 1.5 wt.% or 1.8 wt.%, or as high as or about 3.0 wt.%, 2.7 wt.% or 2.5 wt.%, relative to the total weight of the composition.

[0064] Examples of suitable amounts of components (A), (B) and (C) in the laser-weldable fiber-reinforced polyester composition according to the present invention are as follows:

[0065] - 100 pbw of (A), 100 pbw of (B) and 2.0 pbw of (C); corresponding to 49.505 wt.% of (A), 49.9 wt.% of (B) and 0.990 wt.% of (C);

[0066] - 100 pbw of (A), 100 pbw of (B) and 3.75 pbw of (C), corresponding to 49.080 wt.% of (A), 49.080 wt.% of (B) and 1.840 wt.% of (C);

[0067] - 100 pbw of (A), 15 pbw of (B) and 2.0 pbw of (C), corresponding to 85.470 wt.% of (A), 12.821 wt.% of (B) and 1.709 wt.% of (C);

[0068] - 100 pbw of (A), 15 pbw of (B) and 3.75 pbw of (C), corresponding to 84.211 wt.% of (A), 12.632 wt.% of (B) and 3.158 wt.% of (C);

[0069] - 100 pbw of (A), 35 pbw of (B) and 3 pbw of (C), corresponding to 72.464 wt.% of (A), 25.362 wt.% of (B) and 2.174 wt.% of (C); and

[0070] - 100 pbw of (A), 70 pbw of (B) and 2.3 pbw of (C), corresponding to 58.038 wt.% of (A), 40.627 wt.% of (B) and 1.335 wt.% of (C).

[0071] Herein, the weight percentages (wt.%) are relative to the total amount of components (A), (B) and (C). When no further components are present in the composition, the weight percentages are also relative to the total weight of the composition.

[0072] The composition according to the present invention has high transparency at least at wavelengths commonly used in laser welding processes, more particularly in the near infrared region (NIR) with a wavelength range of 800-1200 nm. In a specific embodiment, the composition has a transparency of at least 25.0%, more particularly at least 30.0%, and even more particularly at least 40% measured at 1.2 mm thickness and 980 nm by the procedure described in the TMG3 User Manual Version 3.0 (referred to herein as the method according to TMG3, and further referred to below (experimental part)). In another specific embodiment, as further described below, the composition has a transparency of at least 15.0%, more particularly at least 17.5%, and even more particularly at least 20.0% measured at 2.0 mm thickness and 980 nm by the method according to TMG3. Herein, the transparency of injection molded plates of different thicknesses of 1.2 mm (75×50 mm plate), 2.0 mm or 3.0 mm (80×80 mm plate) was measured. Injection molding was carried out under standard PBT molding conditions.

[0073] In the visible region (VR) at wavelengths in the range of about 400-700 nm, the transmittance of the composition can vary over a wide range and may be as high as in the NIR, but may also be much lower, depending on the presence of further additives.

[0074] The laser-weldable fiber-reinforced polyester composition of the present invention may optionally contain one or more further additives in addition to components (A), (B) and (C). These one or more further additives are collectively referred to herein as component (D). These one or more further additives may be any auxiliary additives used in fiber-reinforced polyester compositions. Examples thereof are particulate fillers, such as glass beads, amorphous silica, asbestos, calcium silicate, calcium metasilicate, magnesium carbonate, kaolin, chalk, quartz powder, mica, barium sulfate and feldspar; other fibers, i.e. fibers other than glass fibers, such as aramid fibers and potassium titanate fibers; processing aids; stabilizers, such as heat stabilizers, light stabilizers and antioxidants; lubricants and release agents; colorants, such as dyes and pigments; and plasticizers, etc.

[0075] During the preparation of the composition, one or more additives may be added at any desired stage by any suitable conventional means. Herein, the additives may be added, for example, alone, or as a premix with one or more other components, or as a masterbatch. Suitably, the one or more additives are added in the form of a masterbatch comprising the one or more additives dispersed in the PBT resin.

[0076] The amount of one or more further additives of component (D) is preferably such that they do not enhance or only enhance to a limited extent the laser light transparency and / or the mechanical properties of the composition. Suitably, the polyester composition of the invention comprises component (D), if any, in an amount of up to 20 wt.%, preferably up to 15 wt.%, and most preferably in the range of 0-10 wt.%, relative to the total weight of the composition. If particulate fillers are used, they are present in an amount of up to 15 wt.%, preferably up to 10 wt.%, and more preferably in the range of 0-5 wt.%, relative to the total weight of the composition. If other fibers are used, they are also suitably present in an amount of up to 15 wt.%, preferably up to 10 wt.%, and more preferably in the range of 0-5 wt.%, relative to the total weight of the composition.

[0077] Still more preferably, the total amount of particulate fillers and other fibers is in the range of 0-15 wt.%, even more preferably 0-10 wt.%, and most preferably 0-5 wt.%, relative to the total weight of the composition. In addition, fibers and fillers with high laser light absorption, such as carbon fibers, carbon black, graphite, graphene or carbon nanotubes, are preferably present in an amount of less than 1 wt.%, more preferably in an amount in the range of 0-0.25 wt.%, and particularly preferably in an amount in the range of 0-0.05 wt.%, relative to the total weight of the composition.

[0078] Suitably, the composition according to the invention consists of:

[0079] - component (A) in an amount ranging from 40 to 85 wt.%;

[0080] - component (B) in an amount ranging from 15 to 49.5 wt.%;

[0081] - component (C) in an amount ranging from 1 to 3.3 wt.%;

[0082] - component (D), in an amount ranging from 0 to 20 wt.%;

[0083] Herein, weight percentage (wt.%) is relative to the total weight of the composition.

[0084] The composition according to the invention may be neutral in colour, ie comprise no colouring agent, or may be coloured, ie comprise a colouring agent, such as a pigment or a dye.

[0085] Both organic and inorganic pigments and / or dyes are suitable as colorants. Inorganic pigments such as titanium dioxide, ultramarine, iron oxide and carbon black, and also organic pigments such as phthalocyanines, quinacridones, perylenes and dyes (e.g. nigrosine and anthraquinone) can be added as colorants and other colorants if these do not absorb in the range of the laser used. Otherwise, they can only be used in very small amounts to ensure that transmission of at least part of the laser light is still possible. Colorants such as soot and carbon black can be used, but preferably only in very small amounts: preferably 0.1 wt.%, more preferably less than 0.05 wt.%, relative to the total weight of the composition.

[0086] Examples of inorganic pigments are antimony trioxide, antimony pentoxide, basic lead carbonate, basic lead sulfate or lead silicate, lithopone, titanium dioxide (anatase, rutile), zinc oxide, zinc sulfide, metal oxides such as Berlin blue, lead chromate, lead sulfochromate, chromium antimony titanate, chromium oxide, iron oxide, cobalt blue, cobalt chrome blue, cobalt nickel gray, manganese blue, manganese violet, molybdenum orange, molybdenum red, nickel antimony titanate and ultramarine, metal sulfides (such as antimony trisulfide, cadmium sulfide, cadmium sulfoselenide), zirconium silicate, zirconium vanadium blue, zirconium praseodymium yellow.

[0087] Examples of organic pigments are anthraquinone, azo, azomethine, benzanthrone, quinacridone, quinophthalone, dioxazine, flavanthrone, indanthrone, isoindolinone, isoindolinone, methenone, perinone, perylene, phthalocyanine, pyranthrone, pyrrolopyrrole, thioindigo pigments, and metal complexes of dyes such as azo, azomethine, methenamine, or methenamine, or azo compounds of dyes such as azo, azomethine, or methenamine.

[0063] The dyes of the present invention are preferably metal salts of metal complexes of compounds of the invention, azomethines, quinacridones, dioxazines, isoindolinones, perylenes, phthalocyanines, pyrrolopyrroles and thioindigo colorants and bismuth vanadates, anthraquinone series, for example alkylamino, amino, arylamino, cyclohexylamino, hydroxyl, hydroxyamino or phenylthioanthraquinones, triphenylmethane dyes, and fluorescent dyes, for example those from the benzothiazole, coumarin, oxarin or thiazine series, pyrazolones, peronones and anthraquinonemethines, azo and coumarin types.

[0088] In a specific embodiment, the laser-weldable fiber-reinforced polyester composition according to the present invention comprises a laser light transparent colorant. A laser light transparent colorant is understood herein as a colorant that absorbs light in the visible region with a wavelength of less than 800 nm and transmits light in the infrared region with a wavelength of 800 nm to 1200 nm.

[0089] Suitably, the composition comprises the laser light transparent colorant in an amount ranging from 0.1 to 3 wt.%, preferably 0.2 to 2.0 wt.%, more preferably 0.3 to 1.5 wt.%, relative to the total weight of the composition.

[0090] The laser light transparent colorant in a particular embodiment of the present invention may be any color, or a combination of colorants of different colors. Suitably, the laser light transparent colorant is a black colorant or a non-black colorant, or any combination thereof. The non-black laser light transparent colorant may have any color, for example: a red colorant, a yellow colorant, a green colorant, a blue colorant, or a violet colorant.

[0091] In a preferred embodiment of the present invention, the laser weldable fiber reinforced polyester composition comprises a single black laser light transparent colorant, or a combination of a black laser light transparent colorant and at least one non-black laser light transparent colorant, or a combination of at least two non-black laser light transparent colorants providing a black color. Such a combination of at least two non-black laser light transparent colorants providing a black color is also referred to herein as a 'black coloring combination'.

[0092] Black is understood herein as a color having an L*-value of at most 35, measured according to the method of ISO 7724-1-2-3. Thus, a 'black coloration combination' of colorants is understood herein as a colorant combination that provides a color having an L*-value of at most 35, measured according to the method of ISO 7724-1-2-3, to a composition comprising said colorant combination.

[0093] More preferably, the composition comprises a black coloring combination of two or more different non-black laser light transparent colorants. The advantage of a composition comprising a black coloring combination of two or more different non-black laser light transparent colorants is that moldings with a black impression (comparable to coloring with soot) and very good surface quality can be produced, the composition retains high laser light transparency in the range of non-colored materials and is suitable for many welding applications requiring dark or black parts.

[0094] Such black coloring combination suitably comprises a mixture of colorants with different colors, i.e., colorants that absorb different wavelengths in the visible light region below 800nm. There are many examples of the combination of mixed colorants, which can be used to produce black coloring combinations. For example, examples of dyes that can be used as non-black laser light transmission colorants in such combinations are described in EP1240243A1. In general, dyes that present blue, purple and green can be used as the main component for producing black dyes. For example, a combination of blue dye, red dye and yellow dye can be used; a combination of green dye, red dye and yellow dye; a combination of blue dye, green dye and red dye and yellow dye; and a combination of green dye, purple dye and yellow dye. Its example is a combination selected from the following dyes: pyrazolone; purple ring ketone; anthraquinone, such as anthraquinone green dye, anthraquinone blue dye or anthraquinone violet dye; formazan, azo and coumarin types; metal-containing pigments, such as inorganic pigments; metal complexes of azo, azomethine or formazan dyes, azomethine, quinacridone, dioxazine, isoindoline, isoindolinone, perylene, phthalocyanine, pyrrolopyrrole and thioindigo types; quinophthalone dyes; metal azo. More particularly, neutral anthraquinone dyes imparting blue, purple or green can be used by mixing with red and then with yellow dyes as the main component of the resulting black coloring combination. Dyes belonging to monoazo complex dyes can be mixed with anthraquinone dyes to produce black dyes, used as colorants in the composition. In other black coloring combinations, the colorant amine salt of anthraquinone dye can be combined with a second dye selected from purple ring ketone dyes, monoazo complex dyes, anthrapyridone dyes and anthraquinone dyes.

[0095] Suitably, the composition comprises a black colored combination of at least two laser light transparent colorants in a total amount in the range of 0.1-3 wt.%, preferably 0.2-2.0 wt.%, more preferably 0.3-1.5 wt.%, relative to the total weight of the composition.

[0096] In a preferred embodiment, a composition comprising a black colored combination of at least two non-black laser light transmissive colorants has a transmission of at most 10% in at least a spectral sub-range in the VIS spectral range (wavelength of light ranging from 400 nm to 700 nm).

[0097] In a further preferred embodiment of the present invention, the laser transparent fiber reinforced polyester composition is a black composition having an L*-value of at most 35, preferably at most 33, more preferably at most 32. Herein, the value of the color parameter L* is measured by the method according to ISO 7724-1-2-3. For completely black materials, the lower limit of L is 0, preferably L is at least 5.

[0098] In a particularly preferred embodiment, the composition according to the invention is a black composition having a transparency of at least 25.0%, more particularly at least 30.0%, and even more particularly at least 40%, measured at 1.2 mm thickness and 980 nm by the method according to TMG3 as further described herein below. Even more preferably, the composition further has a transparency of at least 15.0%, more particularly at least 17.5%, even more particularly at least 20.0%, measured at 2.0 mm thickness and 980 nm by the method according to TMG3 as further described herein below.

[0099] The present invention also relates to a method for preparing the laser-weldable fiber-reinforced polyester composition of the invention. As described above, the composition and its specific and preferred embodiments can be prepared by methods known per se: by melt mixing the starting components (A), (B) and (C) and optionally component (D) in the amounts as indicated above for the composition of the invention or its various embodiments.

[0100] The method according to the present invention comprises melting polybutylene terephthalate resin and mixing (A) 100 parts by weight of polybutylene terephthalate resin; (B) 15-100 parts by weight of glass fibers and (C) 1.75-4.5 parts by weight of an alkali metal salt of a fatty acid having 24-40 carbon atoms. The melt mixing can be carried out in conventional mixing equipment, such as a single screw extruder and a twin screw extruder, a Brabender mixer or a Banbury mixer, and then extruding the same mixture. The extrudate can be cooled and optionally pelletized, granulated, ground or otherwise reduced to particles or fragments. The mixing temperature is suitably 230 to 290°C.

[0101] Each component can be added simultaneously or separately. For example, components (A), (C) and (D) can be added to a first extruder inlet and mixed and heated, and component (B) can be added to a second extruder inlet and combined with the mixed components (A), (C) and (D).

[0102] The present invention also relates to a method for producing a molded part from a laser-weldable fiber-reinforced polyester composition. The method comprises molding a laser-weldable fiber-reinforced polyester composition, which is according to the present invention or any of its specific or preferred embodiments as described herein above, into a preformed shape. The laser-weldable fiber-reinforced polyester composition of the present invention can be molded by methods known per se: the molded part can be made, for example, by injection molding. For such processes, conventional equipment and conventional process conditions can be used.

[0103] The invention also relates to a laser light transparent moulding made of a laser weldable fibre reinforced polyester composition.Herein, a laser weldable fibre reinforced polyester composition is a composition according to the invention, or any of its various embodiments as described herein above.

[0104] The molded parts are suitable for producing laser welded products. The laser transparency of these molded parts is preferably at least 25.0%, more particularly at least 30.0%, and even more particularly at least 40%, measured at 1.2 mm thickness and 980 nm according to the method of TMG3 as further described herein below (experimental part). The molded parts also preferably have a transparency of at least 15.0%, more particularly at least 17.5%, even more particularly at least 20.0%, measured at 2.0 mm thickness and 980 nm according to the method of TMG3 as further described herein below.

[0105] The advantage of these molded parts compared to other molded parts made from other fiber-reinforced PBT compositions with similar laser light transparency but based on other transparency-enhancing additives is not only that they show an overall better balance between laser light transparency and mechanical properties (i.e. tensile strength, tensile elongation at break and / or impact resistance), but also that they require shorter laser welding cycle times to achieve a predetermined level of weld strength or achieve a higher weld strength with a predetermined laser welding cycle time.

[0106] These advantages are further enhanced for compositions having 1.9-4.0 pbw of component (B), even better 2.0-3.75 pbw of component (B), more particularly 2.1-3.5 pbw of component (B), and even more particularly 2.2-3.0 pbw of component (B), relative to 100 pbw of component (A).

[0107] The present invention also relates to a method for producing a composite article by laser welding. Such a method comprises irradiating a laser beam onto the contact surface of a laser light transparent molded part and a laser light absorbing polymer substrate, thereby forming a welded bond between the laser light transparent molded part and the laser light absorbing polymer substrate. The method of laser welding (also called laser transmission welding) and the equipment used therein are known in the art. The basic principles of laser welding are described in the technical literature, for example in Plastverarbeiter 46 (1995) 9, 42-46; Kunststoffe 87, (1997) 3, 348-350; Kunststoffe 87 (1997) 11, 1632-1640; Kunststoffe 88, (1998), 2, 210-212; and Plastverarbeiter 50 (1999) 4, 18-19. For example, examples of such methods and equipment used therein are described in European Patent EP1048439B1.

[0108] In the method according to the invention, a laser light transparent molding is produced from the laser-weldable fiber-reinforced polyester composition according to the invention or any of its various embodiments as described herein above.

[0109] In the method according to the present invention, a molded part made of a laser transparent fiber reinforced polyester composition according to the present invention or any of its specific embodiments as described herein above is combined with a laser light absorbing polymer substrate and a laser welding process is performed to form a combined laser welded article. The laser light absorbing polymer substrate can be any molded part made of any laser light absorbing polymer material. For example, these can be thermoplastic materials, thermosetting materials or composite materials. Preferably, the laser light absorbing polymer substrate is made of a thermoplastic composition, which contains a thermoplastic polymer and has sufficient laser light absorption in the wavelength range used. The thermoplastic polymer in the laser light absorbing polymer substrate is preferably a thermoplastic polymer that is miscible with the PBT in the laser weldable fiber reinforced polyester composition. More preferably, the thermoplastic composition contains a thermoplastic polyester. The thermoplastic polyester can be, for example, PBT, or PET, or PCT, or any mixture or any copolymer thereof. Most preferably, the thermoplastic composition in the laser light absorbing polymer substrate contains PBT.

[0110] The thermoplastic composition can be suitably made laser light absorptive by adding inorganic pigments, organic pigments, or fillers, or other additives, or any combination thereof. Suitable additives are known in the art. Examples thereof are carbon fibers, carbon black, graphite, graphene, and carbon nanotubes. Carbon black and graphite are highly efficient absorbers of laser light. Carbon black or graphite, or a combination thereof, is preferably used in the laser light absorptive substrate.

[0111] For the laser welding method according to the invention, the advantages mentioned above for the molded parts with regard to an overall better balance of laser light transparency and mechanical properties, as well as shorter laser welding cycle times or higher weld strength also apply here.

[0112] The present invention also relates to a composite article comprising a laser light transparent molded part bonded to a laser light absorbing polymer substrate by laser welding. Herein, the laser light transparent molded part laser welded to the laser light absorbing polymer substrate is made of a laser weldable fiber reinforced PBT composition according to the present invention or any of its various embodiments as described above. The advantage of such an article is not only that the laser weldable fiber reinforced PBT composition has an overall better balance in terms of laser light transparency and mechanical properties (as described above), but also that the laser welded article in which the two molded parts are welded together has a higher weld strength when the same cycle time is applied, or the same weld strength can be obtained in a shorter laser welding cycle time.

[0113] In a preferred embodiment of the present invention, the laser light absorbing polymer matrix in the composite article and used in the laser welding process for making the composite article is made of a thermoplastic composition comprising carbon black and / or graphite and polybutylene terephthalate resin (PBT).

[0114] The present invention is further illustrated by the following examples and comparative experiments.

[0115] result

[0116] raw materials

[0117] A1: polybutylene terephthalate with a melting temperature of 224±2°C (measured by a method according to ISO 11357 with a heating ramp °C / min), a relative solution viscosity (RSV) of 2.36±0.04 dl / g (measured by a method according to ISO 307 at a temperature of 25°C and a concentration of 1 g in 100 g of meta-cresol), and a melt volume rate (MVR) of 11.5±1.0 cm3 / 10 min (measured by a method according to ISO 1133 at 250°C, 2.16 kg).

[0118] B1: Glass Fiber: E-glass, standard grade chopped strands for thermoplastic polyester injection molding compounds

[0119] C1: Sodium salt of montanic acid

[0120] C2: Sodium stearate (sodium salt of stearic acid) #

[0121] C3: Sodium myristate (for comparison purposes) #

[0122] C4: Magnesium salt of montanic acid #

[0123] C5: Aluminum salt of montanic acid #

[0124] D1: Black coloring combination of non-black laser light transparent colorants

[0125] Composition T: BASF LUX B4300 G6 #

[0126] Composition Laser light absorbing polymer substrate: PBT TV4 261BK00001 (standard carbon black filled PBT 30wt.% glass fiber grade)

[0127] # C2, C3, C4 and C5 as well as composition T are not according to the invention; and are used herein only for comparative purposes.

[0128]

[0129] complex

[0130] The molding composition was produced in a ZSK25 twin-screw extruder with a flat temperature profile of 250 to 260° C. and pelletized. Components (A), (B) and (D) were premixed and added from the feed port, component (B) was added at the side feeder.

[0131] Molding

[0132] Prior to molding, the material was dried in a vacuum oven with N2 purge at 120°C for 16 hours. To prepare the test specimens, injection molding was performed on a Fanuc-2 injection molding machine (model α-S50iA) equipped with a suitable mold cavity, using a barrel temperature of 260°C and a cavity temperature of 90°C.

[0133] - For the laser light transparency test, a test sample of 75×50 mm and a thickness of 1.2 mm and a test sample of 80×80 mm and a thickness of 2.0 and 3.0 mm, respectively, were prepared.

[0134] - For tensile testing, test specimens according to ISO 527-1A were prepared.

[0135] - For the unnotched impact test, test specimens according to ISO 179 / 1eU were prepared.

[0136] - For the laser welding test, a test sample having the size of a cover for an automotive radar mold housing and a thickness of 1 mm was prepared.

[0137] Laser welding

[0138] The process and equipment described in European patent EP1048439B1 were used, with low, medium and high laser power settings (200W, 250W and 300W; W = Watt), welding speed (1000mm / s, 2000mm / s and 4000mm / s) and clamping pressure (3.1N / (mm 2 )、6.2N / (mm 2 ) and 9.2N / (mm 2 )) is laser welded as shown in Table 5.

[0139]

[0140] Laser light transparency measurement

[0141] Laser light transparency was measured on injection molded test specimens with a thickness of 1.2 mm (75×50 mm plate), 2.0 mm (80×80 mm plate) and 3.0 mm (80×80 mm plate) using a TMG3 measuring device equipped with a laser light source, using light irradiation with a wavelength of 980 nm, by applying the procedure described in the TMG3 user manual version 3.0 (herein referred to as the method according to TMG3). The TMG3 measuring device was provided by LPKF WeldingQuipment GmbH, Alfred-Nobel-Straβe 55-57, 90765 Fürth Germany.

[0142] Mechanical properties

[0143] - The tensile strength and tensile elongation at break were measured by a tensile test carried out at 23°C at a tensile speed of 5 mm / min according to the method of ISO 527-1A (2019).

[0144] - Charpy unnotched impact strength is measured at 23°C by the method according to ISO 179 / 1eU.

[0145] Viscosity

[0146] The relative solution viscosity of the polymers is measured in m-cresol by the method according to ISO 307 at a temperature of 25° C. at a concentration of 1 g in 100 g m-cresol.

[0147] Color parameters

[0148] The color parameter L* was measured on a laser light transmission test plate by the method according to ISO 7724-1-2-3 at 23°C using a Minolta CM-3700d spectrophotometer and a xenon lamp light source.

[0149] Composition and test results

[0150] Tables 1 to 5 report compositions according to the invention (Examples) and compositions of comparative nature (Comparative Experiments) as well as test results obtained using these Examples and Comparative Experiments.

[0151] Table 1. Composition and test results of Example IV and Comparative Experiments AB and U.

[0152]

[0153]

[0154] The test data surprisingly show that the compositions according to the embodiments of the present invention have good results in both laser light transparency and mechanical properties. The laser light transparency of the composition CE-B containing about 1 pbw sodium montanate (component C1) shows a relatively small increase compared to the composition CE-A containing only PBT, glass fiber and additive D but lacking the component C1. However, when the amount of component C1 exceeds 1 pbw, the laser light transparency shows a sharp increase, and for the composition EX-II containing 2.61 pbw component C1, the laser light transparency rises to 3.5-4 times as high as CE-A. For compositions containing C1 in an amount higher than the 2.61 pbw, the laser light transparency level slowly decreases, but even when the content of component C1 is 4.26 pbw (EX-V), the laser light transparency is still higher than CE-B, while the mechanical properties remain at a good level. When the content of component C1 is 4.86 pbw (CE-U), the laser light transparency is slightly lower, but still higher than CE-B, however, the impact resistance has dropped to less than 50% of the impact resistance of comparative experiments CE-A and CE-B.

[0155] Table 2. Composition and test results of comparative experimental CH.

[0156]

[0157]

[0158] Table 3. Composition and test results of comparative experiments C and IM.

[0159]

[0160] Table 4. Composition and test results of comparative experiments A and NS.

[0161]

[0162]

[0163] #) vl = very low

[0164] The mechanical properties of the compositions according to the embodiments of the present invention, i.e., tensile strength, elongation at break, and simply supported beam unnotched impact resistance, are superior to the comparative experiments with the corresponding amounts of sodium stearate (component C2) or sodium myristate (component C3). For all three components C1, C2, and C3, as the respective contents of C1, C2, and C3 increase, tensile strength, elongation at break, and simply supported beam unnotched impact resistance all show a downward trend. However, components C2 and C3 show similar trends, with the difference from component C1 being that the downward trend starts from a lower amount and / or the decrease in the measured values ​​is greater. For component C1, the downward trend starts from a higher content and / or the decrease in the measured values ​​is smaller.

[0165] Furthermore, simple laboratory tests show that the laser light transparency of the comparative experiments corresponding to the compositions based on magnesium montanate (component C4) and aluminum montanate (component C5) is very low, comparable to or even lower than that of the composition of comparative experiment A (CE-A), and certainly much lower than that of the composition of Example IV.

[0166] Some test results are also shown in Figure 1-4 middle.

[0167] Figure 1 . Figure 1 A graphical representation of the laser light transparency measured at 980 nm and 1.2 mm thickness for compositions containing different amounts of N-montanate (Examples EX-I-EX-V and Comparative Experiments CE-A and CE-B) is shown. It can be seen that above 1 phr up to about 2.5 phr, the laser light transparency increases substantially, and above 2.5 phr, the laser light transparency level is 1.2 mm.

[0168] Figure 2 . Figure 2 Shown is a graphical representation of the retention of tensile strength as a function of varying amounts of sodium montanate (C1 ), sodium stearate (C2), and sodium myristate (C3).

[0169] Figure 3 . Figure 3 A graphical representation of the retention of elongation at break as a function of varying amounts of sodium montanate (C1), sodium stearate (C2) and sodium myristate (C3) is shown.

[0170] Figure 4 . Figure 4 A graphical representation of the retention of unnotched impact resistance as a function of varying amounts of sodium montanate (C1), sodium stearate (C2), and sodium myristate (C3) is shown.

[0171] from Figure 2 , 3 As can be seen from Figures 4 and 5, the elongation at break and unnotched impact resistance of sodium stearate (C2) and sodium myristic acid (C3) at 0.5 or 1 pbw content relative to 100 pbw PBT dropped sharply, and at 1.5 pbw content relative to 100 pbw PBT, the tensile strength also dropped sharply. In all three figures, sodium myristic acid (C3) showed slightly better performance than sodium stearate (C2) for compositions with Cx content in the range of 0.5-2.5 pbw relative to 100 pbw PBT. At the same time, the performance of the composition containing sodium montanate (C1) remained better. Even at a sodium montanate (C1) content of 4.5 pbw relative to 100 pbw of PBT, all three properties of tensile strength, elongation at break and unnotched impact resistance are still maintained at a higher level than the composition with a sodium stearate (C2) content of 1.5 pbw relative to 100 pbw of PBT.

[0172] Table 5. Laser light transmission and welding results for Examples III-IV and Comparative Experiments CE-A and CE-T.

[0173]

[0174]

[0175] Table 5 shows the laser light transmission and welding test results of two examples (EX-III and EX-IV) and two comparative experiments (CE-A and CE-T). CE-A is a fiber-reinforced polyester composition without any additives to enhance laser light transparency, while CE-T is a commercially available product with high transparency but unknown composition.

[0176] The data in the table surprisingly show good results for the welding behavior of Examples II and III, which represent compositions according to the invention. In this context, the performance is much better than in the two comparative experiments, which is not surprising considering the lack of additives for laser light transparency in CE-A, but very surprising for CE-T, which itself has a relatively high laser light transparency.

Claims

1. A laser-weldable fiber-reinforced polyester composition comprising: (A) polybutylene terephthalate resin (PBT); (B) glass fibers; and (C) an alkali metal salt of a fatty acid having 24 to 40 carbon atoms; in, Component (B) is present in an amount ranging from 15 to 100 parts by weight relative to 100 parts by weight of component (A), and component (C) is present in an amount ranging from 1.75 to 4.50 parts by weight relative to 100 parts by weight of component (A).

2. The laser-weldable fiber-reinforced polyester composition according to claim 1, wherein the polybutylene terephthalate resin (A) is a PBT homopolymer, or a PBT copolymer containing at least about 85 mol of butene copolymerized units (butylene units) and terephthalate copolymerized units (terephthalate units) and up to about 15 mol of further comonomer copolymerized units (comonomer units), wherein the molar percentages (mol) of butene units, terephthalate units and comonomer units are all relative to the total molar amount of the molar number of butene units, the molar number of terephthalate units and the molar number of comonomer units in the copolymer.

3. The composition according to claim 1 or 2, wherein The polybutylene terephthalate resin (A) has a relative solution viscosity (RSV) in the range of 1.5-2.8 dl / g, herein, the relative solution viscosity (RSV) is measured in m-cresol at a temperature of 25° C. by the method according to ISO 307 at a concentration of 1 g in 100 g of m-cresol.

4. The composition according to any one of claims 1 to 3, wherein Component (B) is present in an amount ranging from 25 to 80 parts by weight (pbw), preferably 30 to 70 pbw, more preferably 35 to 60 pbw, relative to 100 pbw of component (A).

5. The composition according to any one of claims 1 to 4, wherein The alkali metal in component (C) is sodium or potassium, or a combination thereof.

6. The composition according to any one of claims 1 to 5, wherein The fatty acid in component (C) is a fatty acid having 26 to 36 carbon atoms, preferably a fatty acid having 28 to 32 carbon atoms.

7. The composition according to any one of claims 1 to 6, wherein Component (C) is present in an amount ranging from 2.0-3.75 parts by weight (pbw), more preferably 2.1-3.5 pbw, even more preferably 2.2-3.2 pbw, and most preferably 2.3-3.0 pbw relative to 100 pbw of component (A).

8. A composition according to any one of claims 1 to 7, consisting of: - 40-85 wt.% of component (A); - 15-49.5 wt.% of component (B); - 1 to 3.3 wt.% of component (C); and - 0-20 wt.% of one or more additives (component (D); The weight percentage (wt.%) is relative to the total weight of the composition.

9. A composition according to any one of the preceding claims, wherein The composition comprises a laser light transparent colorant, preferably a black laser light transparent colorant, or a black colored combination of two or more different non-black laser light transparent colorants.

10. A composition according to any one of the preceding claims, wherein The composition has a laser light transparency of at least 25.0%, preferably at least 30.0%, and more preferably at least 40% at a thickness of 1.2 mm, or at least 15.0%, preferably at least 17.5%, and more preferably at least 20% at a thickness of 2.0 mm, as measured at 980 nm by the method according to TMG3 as described above.

11. A method for preparing a laser-weldable fiber-reinforced polyester composition by melt mixing, the method comprising melting a polybutylene terephthalate resin and mixing (A) 100 parts by weight of the polybutylene terephthalate resin; (B) 15-100 parts by weight of glass fiber and (C) 1.75-4.5 parts by weight of an alkali metal salt of a fatty acid having 24-40 carbon atoms.

12. The method according to claim 11, wherein: The laser-weldable fiber-reinforced polyester composition is a composition as mentioned in any one of claims 1-10.

13. A method for making a molded part from a laser-weldable fiber-reinforced polyester composition, comprising: A laser-weldable fiber-reinforced polyester composition is molded into a preformed shape, the laser-weldable fiber-reinforced polyester composition comprising: (A) polybutylene terephthalate resin; (B) glass fibers; and (C) an alkali metal salt of a fatty acid having 24 to 40 carbon atoms; Wherein, component (B) is present in an amount ranging from 15 to 100 parts by weight, and component (C) is present in an amount ranging from 1.75 to 4.5 parts by weight, relative to 100 parts by weight of component (A).

14. The method according to claim 13, wherein: The laser-weldable fiber-reinforced polyester composition is a composition as mentioned in any one of claims 1-10.

15. A laser light transparent molded part made of a laser weldable fiber reinforced polyester composition, the laser weldable fiber reinforced polyester composition comprising: (A) polybutylene terephthalate resin; (B) glass fibers; and (C) an alkali metal salt of a fatty acid having 24 to 40 carbon atoms; in, Component (B) is present in an amount ranging from 15 to 100 parts by weight, and component (C) is present in an amount ranging from 1.75 to 4.5 parts by weight, relative to 100 parts by weight of component (A).

16. The laser light transparent molding according to claim 15, wherein: The laser-weldable fiber-reinforced polyester composition is a composition as mentioned in any one of claims 1-10.

17. A method for producing a composite article by laser welding, the method comprising irradiating a laser beam onto contact surfaces of a laser light transparent molding and a laser light absorbing polymer substrate, thereby forming a welded bond between the laser light transparent molding and the laser light absorbing polymer substrate, wherein: The laser light transparent molded part is made of the laser weldable fiber reinforced polyester composition mentioned in any one of claims 1-10.

18. A composite article comprising a laser light transparent molding bonded to a laser light absorbing polymer substrate by laser welding, wherein: The laser light transparent molded part is made of the laser weldable fiber reinforced polyester composition mentioned in any one of claims 1-10.

Citation Information

Patent Citations

  • Welding process and apparatus

    EP1048439B1

  • Laser beam weldable thermoplastic molding materials

    EP1240243A1

  • Laser-weldable resin composition and molded product

    US20080153957A1

  • Thermoplastic molded vehicle light bezel

    US20100227182A1

  • Laser-transparent polyesters

    US20110288220A1